2007
DOI: 10.1007/s11095-007-9314-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the “Skin Reservoir” of Urea by Confocal Raman Microspectroscopy and Reverse Iontophoresis in vivo

Abstract: A source of urea in the skin, unrelated to the concentration circulating in the blood, was strongly suggested by extracted urea flux observed over time and by the Raman spectroscopy. This "urea reservoir" must be removed before systemic urea levels can be non-invasively monitored by reverse iontophoresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
(20 reference statements)
2
31
0
Order By: Relevance
“…Confocal Raman microspectroscopy (CRM) is increasingly used to determine penetration profiles of xenobiotics in the skin due to the fact that it is a non-destructive method and only minimal sample preparation is needed [1,2,3,4,5,6,7,8,9,10,11,12]. Furthermore, it can also be performed in a non-invasive manner and therefore enables in vivo measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Confocal Raman microspectroscopy (CRM) is increasingly used to determine penetration profiles of xenobiotics in the skin due to the fact that it is a non-destructive method and only minimal sample preparation is needed [1,2,3,4,5,6,7,8,9,10,11,12]. Furthermore, it can also be performed in a non-invasive manner and therefore enables in vivo measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The aims included solving the calibration issue in glucose sampling but also exploring other therapeutic monitoring and clinical chemistry applications. The significant amount work performed with glucose, mannitol, valproate, phenytoin, lithium, caffeine, theophylline, urea, iohexol, phenylalanine and other amino acids [65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82] provided an extensive framework to which we owe clear mechanisms of extraction, feasibility and range of applications - pharmacokinetic profiling, non-invasive therapeutic monitoring and skin health - for the technique. Key issues have been identified such as the impact of plasma binding, of kinetics (i.e.…”
Section: Iontophoresismentioning
confidence: 99%
“…As key examples, Sieg et al [66,67,68,69,70,71] and Nixon et al [72] explored the use of an internal standard method to solve the calibration issue, and Leboulanger et al [73,74,75] demonstrated the feasibility of non-invasive therapeutic monitoring of lithium in bipolar patients. An interesting development was the exploitation of the skin reservoir [76,77,78,79,80,81,82]. Reverse iontophoresis had been initially proposed as a non-invasive method to obtain systemic levels of drugs and markers, therefore the local ‘reservoirs' found for glucose, lithium, urea, lactate and many amino acids [69,70,71,72,73,77,79,81,82] were considered a drawback.…”
Section: Iontophoresismentioning
confidence: 99%
See 2 more Smart Citations